Gambaran Tingkat Pengetahuan Perawat tentang Patient Safety - Hendra Priyatnanto; Fajar Yousriatin; Nurul Jamil (Malahayati Nursing Journal, 2024)
ABSTRACT Patient safety is the most important basis and indicator in providing good health services. Patient safety means ensuring that during the process of providing health services the safety and security of patients is guaranteed. To achieve a high patient safety rate, of course, it is obtained from health service providers who have knowledge regarding patient safety. The aim of this research is to determine the description of nurses' knowledge about patient safety. The research was conducted using a quantitative design with a descriptive approach. The population of this research are nurses in North Kayong Regency with a sample size of 48 respondents. The tool used for data collection uses a questionnaire. The research results showed that the level of knowledge of nurses with good criteria was 35 people (72.9%), and with sufficient criteria there were 13 people (27.1%). Based on the results above, it can be concluded that the majority of nurses' knowledge level about patient safety is in the good category. This is supported by level of education, work period of 1-5 years, and history of having participated in patient safety outreach.  Keywords: Patient Safety, Nurse, Level of Knowledge ABSTRAK Keselamatan pasien (patient safety) merupakan dasar dan indikator paling utama dalam pemberian pelayanan kesehatan yang baik. Keselamatan pasien artinya memastikan bahwa selama proses pemberian pelayanan kesehatan keamanan dan keselamatan pasien terjamin. Untuk mencapai angka keselamatan pasien yang tinggi tentunya didapatkan dari pemberi pelayanan kesehatan yang memiliki pengetahuan terkait keselamatan pasien. Adapun tujuan penelitian ini adalah untuk mengetahui gambaran pengetahuan perawat tentang keselamatan pasien (patient safety). Penelitian dilakukan menggunakan desain kuantitatif dengan pendekatan deskriptif. Populasi penelitan ini merupakan perawat di Kabupaten Kayong Utara dengan jumlah sampel 48 responden. Alat yang digunakan untuk pengumpulan data menggunakan kuisioner. Hasil penelitian didapatkan tingkat pengetahuan perawat dengan kriteria baik berjumlah 35 orang (72.9%), dan dengan kriteria cukup berjumlah 13 orang (27.1%). Berdasarkan hasil diatas disimpulkan bahwa sebagian besar tingkat pengetahuan perawat tentang patient safety berada pada kategori baik. Hal ini didukung oleh tingkat pendidikan, masa kerja 1-5 tahun, dan riwayat pernah mengikuti sosialisasi patient safety.Kata kunci: Patient Safety, Perawat, Tingkat Pengetahuan